Interference Mitigation through Successive Cancellation in Heterogeneous Networks. (23rd January 2013) - Sahin, Onur; Li, Jialing; Lu, Enoch; Li, Yingxue; Pietraski, Philip J.
Abstract : We present a practical interference management scheme for heterogeneous networks (HetNets). The underlying ideas are based on (i) Han-Kobayashi-type message splitting (MS) where the receivers decode and cancel "part" of the interference which is accordingly optimized by the transmitters to ensure decoding and (ii) opportunistic interference cancellation (OIC) where the interfering transmitters act independently of the receivers that employ interference cancellation. We develop a novel transmission and reception scheme, called joint MS and OIC (MS-OIC), that engages both MS and OIC to account for a practical HetNet system with multiple macrocells and femtocells. The MS component includes a precoder design that judiciously maximizes the weighted sum throughput via the enabling of interference cancellation. A system design along with a novel scheduler that facilitates MS-OIC in a general HetNet system is also developed. System level simulations for a general HetNet system are presented, and the proposed MS-OIC scheme is compared with benchmark schemes such as Coordinated Beamforming (CBF) and joint CBF and Almost Blank Subframes (CBF-ABS). It is observed that the proposed MS-OIC scheme improves the macrocell throughput substantially, balances the achievable rates between the macrocell and femtocell users, and provides significant outage performance improvement in the system.